CEO Duality, Ownership, and Readability of Financial Statement Footnotes: Some Evidence from Indonesia - Tubagus Algan Roiston; Iman Harymawan (Jurnal Dinamika Akuntansi dan Bisnis, 2022)
This study examines the association between CEO duality, CEO ownership and financial footnotes readability. The data were collected from 1,469 non-financial firms listed on the Indonesian Stock Exchange (IDX) between 2010 and 2018. Using ordinary least squares (OLS) regression, this study unveiled a negative and significant relationship between CEO duality and financial statement footnotes. In addition, the relationship between CEO ownership and financial statement footnotes is positive and significant. Furthermore, this indicates that CEO duality expands the embarrassment and provokes opportunistic behaviour from the CEO to prioritize personal interests by exploiting potential company resources to weaken the independence of the CEO. Hence, the readability of financial footnotes is undecipherable. On the other hand, CEO ownership is more responsible for improving corporate performance, so more financial statement footnotes are readable. Therefore, this study contributes to the literature on seeking the understanding of the readability of a firm's written communication in emerging countries.